Macroalgal blooms affect the food web of tropical coastal ecosystems impacted by fisheries. (February 2023) - Lane-Medeiros, L.; Puppin-Gonçalves, C.T.; Angelini, R.; Lira, A.S.; Lucena-Frédou, F.; Freire, F.A.M.
Abstract: Macroalgal bloom events have been frequent in recent years. Eutrophication and overexploitation fishing may favor blooms through nutrient availability and capturing top predators. We aim to investigate the drivers of the macroalgae blooms and their consequences on the food web of the two tropical coastal ecosystems: Porto do Mangue (with high macroalgae production) and Baía Formosa (control environment, without macroalgae), both exploited by artisanal fisheries in northeastern Brazil. The food webs are modeled using the Ecopath with Ecosim (EwE) approach. Our results suggest that fishing did not favor macroalgae blooms but rather the high concentration of nutrients added to the semi-arid conditions. Furthermore, the macroalgae bloom showed low trophic impact, so much of their biomass is transferred into detritus. However, when it decomposes, this accumulation of matter alters the structure and functioning of the ecosystem, affecting its main fish resources: shrimp and piscivorous fish. Investigating blooms is key to management. Highlights: Macroalgae bloom can affect coastal food web and fishery production. We compare two tropical marine food webs, with and without macroalgae production. A high nutrient load causes the macroalgae bloom. The macroalgae bloom are little consumed by the fauna, being deposited in the sediment as detritus. Macroalgae bloom have reduced biomass of shrimp, piscivorous fish, and trophic complexity.